A Cultural Competence Organizational Review for Community Health Services: Insights From a Participatory Approach. Issue 3 (May 2017) - Truong, Mandy; Gibbs, Lisa; Pradel, Veronika; Morris, Michal; Gwatirisa, Pauline; Tadic, Maryanne; de Silva, Andrea; Hall, Martin; Young, Dana; Riggs, Elisha; Calache, Hanny; Gussy, Mark; et al.
Cultural competence is an important aspect of health service access and delivery in health promotion and community health. Although a number of frameworks and tools are available to assist health service organizations improve their services to diverse communities, there are few published studies describing organizational cultural competence assessments and the extent to which these tools facilitate cultural competence. This article addresses this gap by describing the development of a cultural competence assessment, intervention, and evaluation tool called the Cultural Competence Organizational Review (CORe) and its implementation in three community sector organizations. Baseline and follow-up staff surveys and document audits were conducted at each participating organization. Process data and organizational documentation were used to evaluate and monitor the experience of CORe within the organizations. Results at follow-up indicated an overall positive trend in organizational cultural competence at each organization in terms of both policy and practice. Organizations that are able to embed actions to improve organizational cultural competence within broader organizational plans increase the likelihood of sustainable changes to policies, procedures, and practice within the organization. The benefits and lessons learned from the implementation of CORe are discussed.